Supervision System for the Management of Regional Revenue and Expenditure Budgets in Makassar City - Ernita Rahmadhani Bym; Andi Pangerang Moenta; Zulkifli Aspan (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
This study aims to analyze the system and mechanism of supervision of the management of the APBD and the form of implementation of the supervision of the management of the APBD in Makassar City. This research was conducted using empirical normative research methods. The data collection technique used is in the form of field research by interviewing related parties and conducting library research. The results showed that the supervision carried out by the DPRD and the Makassar City Inspectorate had not run optimally due to the many shortcomings in the supervision process. The form of implementation of supervision has been carried out well, however, there were many problems found because there were several individuals who made administrative errors such as delays in providing data.